2021
DOI: 10.21203/rs.3.rs-1014562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Work Stress in Nurses Returning To Tertiary A General Hospitals in China After The Delivery of Their Second Child: A Cross-Sectional Study

Abstract: Objective To investigate the current situation of work stress in nurses returning to work in Chinese tertiary A general hospitals after giving birth to their second child and to analyze influencing factors. Methods From January to April 2021, 448 nurses returning to work after the birth of their second child, working in 23 general hospitals in China, were investigated and completed the postpartum work stress scale and self-rating depression scale. Results The total work stress score of returning nurses after g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…When these nurses return after maternity leave, they often face challenges adjusting back into their roles such as con icts between work and family responsibilities, inability to adapt quickly to clinical knowledge updates or work ow changes, di culties coping with high-pressure working environments, fear of making mistakes, and so on [32] . Consequently, the NRWCs experience elevated work pressure leading to higher rates of attrition [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these nurses return after maternity leave, they often face challenges adjusting back into their roles such as con icts between work and family responsibilities, inability to adapt quickly to clinical knowledge updates or work ow changes, di culties coping with high-pressure working environments, fear of making mistakes, and so on [32] . Consequently, the NRWCs experience elevated work pressure leading to higher rates of attrition [5] .…”
Section: Discussionmentioning
confidence: 99%
“…NRWCs face speci c challenges, including work-related stress, time con icts, and breastfeeding di culties due to the unique nature of nursing in hospitals [5] . Studies have shown that support in many aspects is imperative for nurses to overcome these obstacles and adjust to clinical [6,7] .…”
Section: Introductionmentioning
confidence: 99%